The Value of Religious Moderation in the Learning of Islamic Religious Education and Characteristics of Class XI Students at SMK Negeri 1 Lumajang Indonesia - Arifatul Ma’ani; Imam Syaifudin; Nur Avita Khoirunnisa; Bopel Wasianto; Syovinatus Sholicha; Eka Ismaya Indra Purnamanita; Eva Andriani (PT Inovasi Pratama Internasional, 2023)
The number of cases of intolerance that have occurred in Indonesia, especially in educational institutions, shows that there is a lack of tolerance in them. This should be immediately addressed by educational institutions to create conducive school conditions. In the world of education, students are a group that is very prone to being swept up by the currents of religious radicalism. The age is still very young and still unstable with a fiery enthusiasm, as well as the longing to practice religion more thoroughly, making young people the target of radical groups who preach religious understanding and attitudes that are rigid and tend to be shallow. On the other hand, at the same time, religious liberalism has also begun to infiltrate some young people, namely high school students. Because of that, the world of education has a role to fortify students so that they can always be in the middle, not taking sides to the left and right, guiding students to be fair, the middle position makes a person visible to anyone from different angles.